Sistem Audit Teknologi Informasi Berdasarkan Cobit Untuk Menilai Level Of Maturity Berbasis Web: Information Technology Audit System Based on Cobit to Assess Web-Based Level of Maturity - Chotijah, Umi (Technomedia Journal, 2024)
Information and communication technology (ICT), undeniably, plays an important role in the transformation agenda of every company. The Semen Indonesia Group (SIG) is no exception, which requires operational support for digitizing business processes and is part of the strategy to achieve its goals. However, the problem that often occurs in companies is the use of information technology which turns out to be not in accordance with expectations, therefore governance is needed for the use of information technology and information systems. Information technology governance and information systems are needed to maintain and ensure information systems at PT. Semen Indonesia is doing well. The magnitude of the risks that may arise due to the application of information technology makes an information technology audit very important to do. Its purpose is to be a support tool for top management and close the gap between technical issues, business risks and requirements. The method used in the development of building an information technology audit system is waterfall. The framework used is Control Objectives for Information and Related Technology (COBIT). Based on the results of implementation and testing, the information technology audit system is appropriate and meets the predetermined functional requirements of the testing process.